شمس وظلال ‘‘محورية العشق وأبعاده الاستيعابية ‘‘ : قراءة تحليلية في منظومة منطق الطير لفريد الدين العطار - قول, معمر (جامعة الوادي - University of Eloued, 2021)
يُعتبر الإنسان محورا رئيسا في الخطاب الصوفي عموما والفارسي خصوصا ،إذ هو محلّ الخطاب الإلهي ،لذا حاول المتصوفة أن يصوغوا خطابا جامعا مُستوعبا الإنسان بألوانه وأعراقه وأجناسه وألسنته وملله المختلفة، ولطالما شكلت هذه التباينات حاجزا أمام التواصل الإنساني، لذا حاول متصوفة فارس عموما والعطار خصوصا في منظومته منطق الطير أن يصوغوا خطابا محوريا استيعابيا يمكنه أن يكون كالمركز بالنسبة للدائرة، ولما كانت الروح موطنا مُشتركا لجميع الإنسانية كانت المحبّة والعشق هما رأس الخيط، فمادام المعشوق واحدا وهو الحقّ كانت الطرق إليه متعددة، وهذا التعدد لا يقدح في الوحدة بل يؤكدها، فإن فرّقت الوسائل بينهم فقد جمعهم عبير المعشوق ومحبته، وهذا ما يتجلى بشكل كبير في خطاب فريد الدين العطار ومتصوفة فارس أمثال العطار والرومي وسعدي وحافظ الذين اعتبروا أن الاختلافات بين البشر ما هي إلا ظلال متحولة وأن المحبة والعشق شمس خالدة. من هذا المنطلق تحاول هذه الورقة معالجة فكرة العشق ومركزيته في منظومة منطق الطير لفريد الدين العطار النيسابوري ودورها في استيعاب الآخر The human being is considered a main issue in the Sufi discourse generally and Persian in particular, as it is the place of the divine discourse, so the Sufis used to formulate a comprehensive discourse that accommodated man with his different colors, races, races, tongues and deities. His system is the bird’s logic that they formulate a central and accommodating discourse that can be like the center for a circle. Since the soul is a common home for all humanity, love and adoration are the head of the thread. So, as long as the lover is one and he is the truth, the paths to it are multiple; this multiplicity does not undermine unity but rather confirms it. The means between them were brought together by Abir Al-Ma’shouq and his love, and this is clearly evident in the speech of Farid Al-Din Al-Attar and the Sufis of Faris such as Al-Attar, Al-Rumi, Saadi and Hafez, who considered that the differences between human beings are nothing, but transforming shadows and that love and love are an eternal sun. From this point of view, this paper attempted to express the idea of love and its centrality in the logic of the bird by Farid Al-Din Al-Attar Al-Nisaburi and its role in assimilating the other.
Sun and Shadows “Axial Love and Its Absorptive Dimensions“ - Analytical Reading in the system of logic of the bird by Farid Al-Din Al-Attar-
مقال
Keywords: العشق ; الشمس ; الظلال ; التعدد ; ال ; حدة ; العطار; The love; the sun; shadows; plurality and unity; attar;Persia mystics